Factor Structure and Validation of the Undergraduate Teaching Faculty Investment Questionnaire - Sun, Lizhi; Zhang, Hong; Xu, Jingjing (Frontiers in Psychology, 2021)
Undergraduate education is very important for higher education. Among the factors affecting the quality of undergraduate education, teaching quality is the most important factor. At present, an important issue that affects teaching quality is insufficient teaching investment. An open-ended questionnaire survey was conducted on 62 faculty members and 65 university students in China. Results found that the undergraduate teaching investment of faculty members mainly consists of four parts: workload investment, ability investment, energy investment, and teaching emotional investment. A preliminary test was conducted on 342 faculty members, and the results of an exploratory factor analysis supported the proposed four-dimensional teaching investment model. The test involved 293 faculty members and confirmatory factor analysis showed that the four-dimensional model had a good degree of fit. A further criterion-related test showed that the four-dimensional teaching investment of faculty members has a significant positive correlation with classroom management, clarity of teaching materials, teacher–student interaction, teaching strategies, and skills application, and work engagement. These results show that the proposed four dimensions of teaching investment effectively measure the teaching investment of faculty members, specifically the indicators of teaching investment and that they promote the development of faculty teaching investment research.